Gaas/algaas nanoheterostructures: simulation and application on high mobility transistors (2011)
This work analyses the features of GaAs/AlGaAs heterostructure, highlighting semiconductor junction properties. Charge confinement was produced when two materials having different band-gap were fixed; such high electron concentration is called two-dimensional electron gas (2DEG). Device simulation for smart integrated systems (DESSIS) is simulation software which uses physical models and robust numerical methods for simulating semiconductor devices and 3-5 element heterostructures. Results for different heterostructure doping profiles and voltages are presented in this work.  High electron mobility transistors (HEMTs) are one of the most important applications for heterostructures; they work on 30 to 300 GHz frequency ranges. These transistors are simulated in this work; a 1 A/mm2 high current density was obtained in the channel, such value being comparable to other values reported for similar transistors.